2019
DOI: 10.1042/bsr20190770
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the scope of candidate prognostic marker IGFBP2 in glioblastoma

Abstract: Glioblastoma is the most common malignant brain tumor in adults. Unfortunately, it has a very poor prognosis and no cure. In a recent paper by Yuan et al. (Bioscience Reports (2019), DOI:10.1042/BSR20190045) RNAscope was used to detect insulin-like growth factor binding protein 2 (IGFBP2) mRNA in glioblastoma biopsies. The study revealed that patients with high levels of IGFBP2 mRNA had shorter survival and that IGFBP2 transcript level was an independent prognostic factor. It is also of value to determine the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 19 publications
(37 reference statements)
2
9
0
Order By: Relevance
“…Insulin-like growth factor binding protein 2, a well-established molecule of interest in GBM ( Yao et al, 2016 ), was found to be more highly expressed in STS and to have an impact on overall survival. IGFBP2 expression is said to be higher in all four (classical, mesenchymal, proneural, and neural) GBM subtypes ( Lindström, 2019 ). It also drives gene programs for immunosuppression in the mesenchymal subtype and is suggested as an immunotherapeutic target ( Liu et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Insulin-like growth factor binding protein 2, a well-established molecule of interest in GBM ( Yao et al, 2016 ), was found to be more highly expressed in STS and to have an impact on overall survival. IGFBP2 expression is said to be higher in all four (classical, mesenchymal, proneural, and neural) GBM subtypes ( Lindström, 2019 ). It also drives gene programs for immunosuppression in the mesenchymal subtype and is suggested as an immunotherapeutic target ( Liu et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…In non-mesenchymal subtypes (classical, proneural, and neural), it modulates cell proliferation ( Phillips et al, 2016 ; Cai et al, 2018 ). It has also been found to be a marker of tumor aggressiveness and a prognostic marker for survival ( Lindström, 2019 ). However, the molecular mechanism by which IGFBP2 affects disease progression and patient prognosis is not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the anatomy of brain tissue causes difficulties with drug administration [6,7]. Therefore, it is not surprising that the median survival of diagnosed GBM patients ranges between 12 and 14 months, and has not changed considerably over the years [1,8,9]. Recently, numerous growth factors (EGF, TGF-β) and cytokines (e.g., IL-6) have been reported to support tumor growth and spreading [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, a rapid development of invasiveness/drug-resistance after therapeutic cycles determines the swift recurrences of GBM [ 15 , 16 , 17 , 18 , 19 , 20 ]. The median survival time of diagnosed GBM patients ranges between 12 and 14 months, and it remained constant over the recent decades [ 21 , 22 ]. Accordingly, the effective GBM treatment is regarded as the most prominent challenge for contemporary neurooncology.…”
Section: Introductionmentioning
confidence: 99%